Design of three step joint typologies: review of european standardized approaches - Branco, Jorge M. (2018)
When assessing timber roof structures on-site for any restoration project, engineers can be faced with elements that, over time, were poorly preserved, especially damaged joints in contact with moist masonry walls. Before dealing with any intervention technique, the mechanical behaviour of such carpentry connections must be properly understood. Therefore, it has to be determined how the joints fail, which parameters (i.e. geometrical configurations and mechanical properties of the joint) influence the appearance conditions of failure modes, and the way how the internal forces are distributed within the connection. Therefore, the present paper aims at overviewing three different typologies of Step Joints (SJ) which can often be encountered within traditional timber carpentries between the rafter and the tie beam: the Single Step Joint, the Double Step Joint, and the Single Step Joint with Tenon-Mortise. Regarding each SJ typology, some design rules and geometrical recommendations can be gathered from European Standards and from authors of works on the subject, but no design equation is conventionally defined. Hence, new design models have been determined through the Analytical Campaign for the investigated Step Joints according to their geometrical parameters and to both failure modes: the shear crack in the tie beam and the crushing at the front-notch surface. In order to check the reliability of new design models and the emergence conditions of both failure modes, future experiments and numerical analysis on the three SJ typologies are going to be performed.